2004
DOI: 10.1108/13620430410550763
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a career: women architects at work

Abstract: Constructing a Career: Women Architects at Work AbstractUsing data from 37 interviews carried out with female architects in Britain, this paper examines how they have constructed their careers in a male-dominated profession. The findings indicate that there is a significant rejection of the 'traditional' career within an organisation, instead there is diversity in the forms of work organisation adopted especially with regard to the desire for control over career and working life. KeywordsWomen's careers; self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
15
0
3
Order By: Relevance
“…Accordingly, researchers (Grant‐Vallone & Ensher, ; Valcour & Ladge, ) have suggested that professional women are constructing a career model that includes periods of unemployment and part‐time work throughout their child‐bearing years. Such accommodations are consistent with a protean career orientation that allows professional women to work towards career success that coincides with their personal values (Cabrera, ; Caven, ).…”
supporting
confidence: 54%
“…Accordingly, researchers (Grant‐Vallone & Ensher, ; Valcour & Ladge, ) have suggested that professional women are constructing a career model that includes periods of unemployment and part‐time work throughout their child‐bearing years. Such accommodations are consistent with a protean career orientation that allows professional women to work towards career success that coincides with their personal values (Cabrera, ; Caven, ).…”
supporting
confidence: 54%
“…Much of the empirical work examining female architects' under-representation has focussed on the impact that having a child has on a woman's career (Caven, 2005, deGraft Johnson et al, 2005Fowler and Wilson, 2004), with much appearing to assume that men and women are two distinct homogeneous groups. In reality, there are multiple masculinities, specifically hegemonic masculinities and subordinate masculinities (Collinson and Hearn, 1994).…”
Section: The Architectural Professionmentioning
confidence: 99%
“…Architects work in the construction industry, a sector which exhibits a highly masculine working environment where women (Ness, 2012, Watts, 2007 and marginalised men (Denisson, 2010) experience difficulties participating fully in the labour market. Despite a body of literature identifying the difficulties faced by women architects (Caven, 2005;Fowler andWilson, 2004, deGraft Johnson et al, 2005), male architects remain unexamined. Understanding masculinities can develop gender research beyond essentialist approaches that emphasise male and female.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies show that the problems faced by women in construction are starting to be understood (Caven, Navarro Astor & Diop, 2012), albeit mainly from the multiple and varied perspectives of women in the industry (c.f., Caven, 2004Caven, , 2006Fowler & Wilson, 2004;Greed, 2006). Analyses focusing on institutions and discourse and their role in policy outcomes are notable by their absence.…”
Section: Industry Level -The Implementation Of Gender Diversity Initimentioning
confidence: 99%